El metateatro y la dramática de Vargas Llosa : Hacia una poética del espectador. - Rivera-Rodas, Oscar (John Benjamins Pub. Co., 1992)
Rivera-Rodas proposes a new concept about what he calls the poetics of the theatrical reception. The discussion of this phenomenon, which also deals with metatheater, focuses on the dramatic work of Mario Vargas Llosa. Examination of the complex relationships of contemporary dramatic structures provides a new definition of metatheater and its effects on the public. Metatheater is shown as a semiotic result not theatrically representable, since it takes place only in the spectator's perceptible experience. Therefore, it does not exist prior to the theatrical or reading reception, nor is it pres.